2011
DOI: 10.1016/j.jmii.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an outbreak of Serratia marcescens in a neonatal intensive care unit

Abstract: Present investigation suggested that an outbreak of S marcescens infection was caused by a major clone in our NICU, possibly transmitted through the hands of HCWs, emphasizing that strict hand washing before and after contact with patients must be the rule of the thumb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…However, solutions similar to ours have also been reported . According to earlier studies, S. marcescens can spread uncontrollably and contaminate the environment and instruments such as nursing equipment, ventilators and breastmilk . In the present study, we only took three environmental samples, from the faucet and ventilator, and these remained negative.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, solutions similar to ours have also been reported . According to earlier studies, S. marcescens can spread uncontrollably and contaminate the environment and instruments such as nursing equipment, ventilators and breastmilk . In the present study, we only took three environmental samples, from the faucet and ventilator, and these remained negative.…”
Section: Discussionsupporting
confidence: 79%
“…A specially assigned team was established to care for the infected or colonised neonates, but the staff were not screened, as healthcare workers are considered vectors, but not ultimate sources, of Serratia outbreaks . As mentioned above, S .…”
Section: Discussionmentioning
confidence: 99%
“…(particularly Enterobacter cloacae and Serratia marcescens ) are important nosocomial pathogens and outbreaks caused by these organisms have been documented. Cross‐transmission via transient contamination of HCWs’ hands has also been well documented in epidemic and endemic situations and outbreaks of bacteraemia involving both species have also been linked to contaminated medical products . Contamination both of dry surfaces and moist environments was particularly frequent when looked for, suggesting that environmental contamination played a central role in many outbreaks.…”
Section: Mechanisms Of Transmissionmentioning
confidence: 99%
“…Mature milk may have its color altered according to the diet of the nursing mother or by the use of medications, for example, milk with a greenish coloration due to a diet rich in riboflavin [10,16]. The "dark green" coloration is caused by the bacterium of the genus Pseudomonas, and the "brick red" coloration, may be due to the suspicion of blood in the milk by papillary discharge or nipple injury, or by the presence of the bacterium Serratia marcescens, making such sample unfit for human consumption [10], since this bacterium has been the causative agent of infections in children hospitalized in NICU [19]. In a study that investigated an outbreak of Serratia marcescens in an NICU in Turkey, it suggested the possibility of contamination through rHM, although it was not statistically correlated [19].…”
Section: Discussionmentioning
confidence: 99%